Water flow in soils - Miyazaki, Tsuyoshi 1947- (Books in soils, plants, and the environment, 2006)
Conveys the fundamental concepts of water flow in soils with nonmathematical explanations. This book elucidates the basic and advanced principles of water movement in soils.